FOOD SAFETY STUDY IN TERMS OF MICROBIOLOGY IN PORK SATAY IN SANGEH TOURISM VILLAGE - Ditiarini, Ni Putu Vriska Putri; Sudita Puryana, I Gusti Putu; Tamam, Badrut (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
The application of tourism health, such as food safety, is an important matter to pay attention to. Based on the annual report (BPOM, 2019), there are 373 cases of food poisoning in Bali, so Bali ranks fourth with the highest cases of food poisoning in Indonesia. The type of research used is observational. This research was conducted by testing samples to determine microbial contamination on pork satay as well as observing and recording food safety scores where pork satay is sold. The design used was cross-sectional because all research subjects were observed at one time. Food safety scores were tested, and TPC, MPN, and E. coli were tested so that 9 samples (56.25%) were categorized as vulnerable to safe consumption. 16 samples of pork satay met the minimum requirements for microbial contamination, ranging from 20/g to 60,000/g. 1 sample of pork satay (6.25%) with the amount of coliform contamination exceeding the standard, namely 438/gr. There were 6 samples of pork satay (37.5%) positive for E. coli. Based on the results of the Kruskal-Wallis test for total microbial contamination based on the food safety score, the results showed that there was a difference in the results of the microbial contamination test and E. coli with a food safety score. Coliform bacteria contamination based on the food safety score showed that there was no difference from the results of the MPN test with the food safety score based on the Asymp.sig value 0.05. Even so, there are still many traders who have not implemented personal hygiene, so it is necessary to carry out food safety training, monitoring, and developing food quality on a regular basis.